Characterization of primary and secondary magnetite in marine sediment by combining chemical and magnetic unmixing techniques - Ludwig, P. (2013)
We present a novel technique for quantitative unmixing of primary and secondary ferrimagnetic minerals in sediments. Hysteresis and high-resolution first-order reversal curve (FORC) measurements are performed on sediment samples before and after digestion in a citrate–bicarbonate–dithionite (CBD) solution optimized for maximum selective extraction of secondary fine-grained iron oxides. The difference between magnetic measurements of untreated and CBD-treated sample materials is used to calculate the original magnetic signature of CBD-extractable minerals. A combination of selective chemical extraction and magnetic measurements suited for the detection of single-domain particles provides a cross-check between chemical and magnetic unmixing of primary and secondary iron oxides and resolves the non-uniqueness problem of numerical unmixing methods. A quantitative magnetic characterization of secondary ferrimagnetic minerals in a magnetofossil-rich pelagic carbonate is presented for the first time. It can be used for calibration of recently developed fast magnetic unmixing techniques. CBD-based Fe extraction from sediments with minimal clastic and/or aeolian inputs, such as pelagic carbonates, is particularly suited for the search for cosmogenic 60Fe signatures from supernova explosions, because 60Fe dilution by dissolved primary Fe-bearing minerals is minimized.